2018
DOI: 10.1002/adfm.201706410
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐Responsive Actuation of a DNA Origami Flexor

Abstract: Nanomachines capable of controlled programmable work at the nanoscale promise to revolutionize a vast range of research and eventually should impact on daily lives. Due to the ease of design and modification, DNA origami is emerging as a natural platform to build such machines. However, one essential challenge is the controlled and rapid actuation of DNA origami using an external biocompatible stimulus. Here, actuation based on temperature‐induced phase transitions of the thermo‐responsive polymer poly(N‐isopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 46 publications
1
91
0
5
Order By: Relevance
“…Thermoplasmonics is an emerging hot topic that offers a route to controllable actuation at the nanoscale and reversible plasmon tuning of sensing devices . The ability to manipulate nanoparticles in order to create and steer nanostructures is essential in many applications such as drug delivery, noninvasive microsurgery, nanoassembly, and fabrication …”
Section: Heating Up the Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermoplasmonics is an emerging hot topic that offers a route to controllable actuation at the nanoscale and reversible plasmon tuning of sensing devices . The ability to manipulate nanoparticles in order to create and steer nanostructures is essential in many applications such as drug delivery, noninvasive microsurgery, nanoassembly, and fabrication …”
Section: Heating Up the Environmentmentioning
confidence: 99%
“…Recent key results have demonstrated that the actuation from the ANTs can be coordinated along a common direction, and that ANTs can power DNA origami constructs . Moreover, the polymer can be grown within the plasmonic hotspots, in a light‐guided and well‐controlled fashion .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach toward the implementation of machine‐like behaviors in DNA origami structures is based on the creation of molecular assemblies, in which multiple origami subunits are connected with each other via simple machine elements such as pivots or hinges . When the subunits are further made to bind with each other through sufficiently weak interactions, which can be reversibly switched by external stimuli, the structural components can change their relative positions, resulting in an overall conformational change.…”
Section: Introductionmentioning
confidence: 99%
“…The stimuli and energy sources for the operation of such devices can be quite diverse, for instance, DNA strand displacement processes, binding of biomolecules through aptamers, environmental changes (e.g., changes in salt concentrations or physical stimuli such as temperature), or electric and magnetic fields . In many cases, “switchability” has been introduced by appropriate chemical modifications of the devices.…”
Section: Introductionmentioning
confidence: 99%